The influence of fiber surface profile and roughness to fiber–matrix interfacial properties. (May 2020) - Putra, Ichsan Setya; Budiman, Bentang Arief; Sambegoro, Poetro Lebdo; Santosa, Sigit Puji; Mahyuddin, Andi Isra; Kishimoto, Kikuo; Inaba, Kazuaki
This work investigates the influence of fiber surface profile and roughness to fiber–matrix interfacial properties. A series of the push-out test is performed using specimens with different fiber surface profile and roughness. Numerical simulation is then carried out by employing a finite element method to fit the experimental data. The model contains an indenter which pushes in a single fiber from the matrix, while the cohesive zone model is applied to represent the interface resulting in force–displacement curves. Our results suggest that continuous cavities formed in graphite-based fiber may not be beneficial to interfacial properties since it can accelerate a debonding process along with the interface. In contrast, scattered cavities on the fiber surface create strong mechanical locking, which increases the interfacial strength. These results broaden the understanding of the surface profile, which would shed light on a new perspective in designing composite structures.